P n ( x ) = i = 0 ∏ n j = 0 ∑ i k = 0 ∏ j l = 0 ∑ k x l
For polynomial P n ( x ) as defined above, compute P 3 ( 1 ) P 2 ( 1 ) P 5 ( 1 ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Problem Loading...
Note Loading...
Set Loading...
Let x = 1 , then:
P n ( 1 ) = ∏ i = 0 n ∑ j = 0 i ∏ k = 0 j ∑ l = 0 k 1 l = ∏ i = 0 n ∑ j = 0 i ∏ k = 0 j ∑ l = 0 k 1 = ∏ i = 0 n ∑ j = 0 i ∏ k = 0 j ( k + 1 ) = ∏ i = 0 n ∑ j = 0 i ( j + 1 ) !
Let's refine this expression a little bit:
P n ( 1 ) = ∏ i = 0 n ∑ j = 0 i ( j + 1 ) ! = ∏ i = 0 n ∑ j = 1 i + 1 j ! = ∏ i = 1 n + 1 ∑ j = 1 i j !
Now that we have a simpler task at hand we can start computing the wanted value:
P 3 ( 1 ) P 2 ( 1 ) P 5 ( 1 ) = ∏ i = 1 4 ∑ j = 1 i j ! × ∏ i = 1 3 ∑ j = 1 i j ! ∏ i = 1 6 ∑ j = 1 i j ! = ∏ i = 1 3 ∑ j = 1 i j ! ∏ i = 5 6 ∑ j = 1 i j ! = = ( 1 ! ) × ( 1 ! + 2 ! ) × ( 1 ! + 2 ! + 3 ! ) ( 1 ! + 2 ! + 3 ! + 4 ! + 5 ! ) × ( 1 ! + 2 ! + 3 ! + 4 ! + 5 ! + 6 ! ) = = 1 × ( 1 + 2 ) × ( 1 + 2 + 6 ) ( 1 + 2 + 6 + 2 4 + 1 2 0 ) × ( 1 + 2 + 6 + 2 4 + 1 2 0 + 7 2 0 ) = = 1 × 3 × 9 1 5 3 × 8 7 3 = 4 9 4 7